PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR MATERI DIAGRAM GARIS SISWA KELAS IV SD SWASTA BABAR SARI PANCUR BATU - Deyrizky Parinduri; Nurhudayah Manjani (Cahaya Ilmu Bangsa Institute, 2025)
This research aims to determine student learning outcomes using the Numbered Head Together model for class IV students and to determine the significant effect of using the Numbered Head Together model for class IV students. The method used in the research is quantitative. The type of research is quasi experimental, the research design used is a one group pretest posttest design. The population of this study was all fourth grade students at Babar Sari Private Elementary School, Pancur Batu, totaling 22 students. Based on the research results, the average pre-test score was x = 52 and the average post-test score was x = 81. To describe the research hypothesis, statistical analysis of independent tests between two factors was used and obtained x^2count = 23.88 and x^2table = 68.058. data freedom 0.05. Because, x^2≥ x^2 (1- ∝)(B-1)(K-1) or x^2 count = 23.88 ≤ x^2 table = 68.058 it can be concluded that there is an influence using the Numbered Head model Together on line diagram material in class IV of Babar Sari Private Elementary School, Paancur Batu.